Changing the landscape: Core Curriculum on Disability Rights for Undergraduate Law Students in Africa - Edited by Pretoria University Law Press (Pretoria University Law Press (PULP), 2015)
About the publication This Core Curriculum on Disability Rights for Undergraduate Law Students in Africa has been developed as part of a broader initiative to foster and strengthen knowledge and awareness about and interest in the rights of persons with disabilities among lawyers in Africa. This initiative, the 'Disability Rights and Law Schools in Africa Project' was supported by the Open Society Foundations, initially the Open Society Initiative for Southern Africa (OSISA) and later complemented by the Higher Education Support Programme (HESP) and the Human Rights Initiative (HRI). For the avoidance of doubt, the curriculum is written with the aim of being delivered to learners undertaking legal studies. It has been designed to assist law faculties in Africa to develop and teach undergraduate courses on disability rights in Africa. The Curriculum, which contains practical examples, notes for lecturers and student activities, may be adapted to suit the circumstances of particular law schools. It will be available as an online resource, to which interested persons may contribute, in order to to keep it updated and relevant. About the editors: The Pretoria University Law Press (PULP) is based at the Faculty of Law, University of Pretoria, South Africa. PULP endeavours to publish and make available innovative, high-quality scholarly texts on law in Africa. PULP also publishes a series of collections of legal documents related to public law in Africa, as well as text books from African countries other than South Africa. Table of Contents Introduction to the curriculum Module 1: Introduction to disability rights Module 2: Protection of disability rights - global framework Module 3: Protection of disability rights under African regional and national law Module 4: Non-discrimination against people with disabilities Module 5: Right to health Module 6: Participation in political and public life Module 7: Employment Module 8: The right to education Module 9: Vulnerabilities and inter-sectionalites Module 10: Legal capacity law and policy Module 11: Access to justice Module 12: National implementation and monitoring of disability rights